Back Cover Image, Volume 33, Issue 4. (1st April 2022) - Kawai, Shunsuke; Mukai, Yasushi; Inoue, Shujiro; Yakabe, Daisuke; Nagaoka, Kazuhiro; Sakamoto, Kazuo; Takase, Susumu; Chishaki, Akiko; Tsutsui, Hiroyuki
Abstract : The back cover image is based on the Original Article Location and coupling interval of an ectopic excitation determine the initiation of atrial fibrillation from the pulmonary veins by Shunsuke Kawai et al., https://doi.org/10.1111/jce.15371 .